PRODUCTION AND DESCRIPTION THE CHARACTERIZATION OF GUAR GUM GALACTOMANNAN BUTYL ETHER - Kazachenko, A. S.; Fetisova, O. Yu.; Antonov, A.V.; Bondarenko, G.N.; Sychev, V.V. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
Guar gum galactomannan is a common polysaccharide isolated from the legume plants Cyamopsis tetraganoloba. Guar gum derivatives are widely used in many industrial fields. In this work, a method for obtaining a new derivative of guar gum, galactomannan butyl ether, is considered. The introduction of the butyl group into the structure of galactomannan was proved by IR spectroscopy, by the appearance of absorption bands in the regions corresponding to the vibrations of the –C – O – C–, CH2 and CH3 groups. According to X-ray diffraction data, it was shown that in the process of obtaining butyl ether of galactomannan, the structure is amorphous. According to the data of scanning electron microscopy, the powder of galactomannan butyl ether has a porous morphology. The pore sizes in the particles of galactomannan butyl ether range from 70 to 300 μm. The obtained galactomannan butyl ether can find application in medicine - as a filler for tablets, in construction - as an additive for adhesives and in other fields.